Analisis Nilai-Nilai Karakter Film Upin dan Ipin Ikhlas dari Hati yang Bermanfaat bagi Penguatan Karakter Anak SD - Widya Sonia Hargiarti; A.Y. Soegeng Ysh; Ari Widyaningum (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
From the context of the research on Upin and Ipin, there are many influences, starting from the moral message that educates students so that they are able to imitate the language contained in the film, namely Malay. The purpose of this study is to analyze the character values in Upin and Ipin's film Ikhlas from the heart. The type of research used is qualitative with a descriptive method. Methods of data collection is done by observation, interviews, questionnaires, and documentation. Checking the validity of the data is done by triangulation. The data analysis technique uses data reduction, data display, and conclusion drawing/verification. The data presentation technique is presented in tabular form. Based on the results of data analysis in this study, it was found that the character values in each scene of the Upin and Ipin film were found. The character values found in Upin and Ipin's film "Ikhlas Dari Hati" include hard work, social care, curiosity, creativity, respect for achievement and communicative/friendly. The teacher can also explain the positive and negative impacts when watching the film and provide guidance on what character values can be imitated by students to practice the value of character education in everyday life.